2016
DOI: 10.1007/s10967-016-5005-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and thermogravimetric analysis of lanthanide hexafluoroacetylacetone chelates

Abstract: This work reports the thermodynamic characterizations of organometallic species as a vehicle for the rapid separation of volatile nuclear fission products via gas chromatography due to differences in adsorption enthalpy. Because adsorption and sublimation thermodynamics are linearly correlated, there is considerable motivation to determine sublimation enthalpies. A method of isothermal thermogravimetric analysis, TGA-MS and melting point analysis are employed on thirteen lanthanide 1,1,1,5,5,5-hexafluoroacetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although traditional solvent extraction and ion-exchange techniques have been largely used for separations of lanthanides and actinides, gas-phase studies are critical for rapid radiochemical separations and efficient capabilities for the prediction of binding selectivity in the gas phase are essential to optimize and design separation agents. Calculations of differences in Gibbs free energy of reaction allow for the prediction of likelihood of binding selectivity and further possible separation selectivity, however, fundamental understanding of complexation preferences from structural characteristics and electron-withdrawing effects can be insightful for the design of targeted extracting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditional solvent extraction and ion-exchange techniques have been largely used for separations of lanthanides and actinides, gas-phase studies are critical for rapid radiochemical separations and efficient capabilities for the prediction of binding selectivity in the gas phase are essential to optimize and design separation agents. Calculations of differences in Gibbs free energy of reaction allow for the prediction of likelihood of binding selectivity and further possible separation selectivity, however, fundamental understanding of complexation preferences from structural characteristics and electron-withdrawing effects can be insightful for the design of targeted extracting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Thermogravimetric analysis is used to study the sublimation process, due to the simplicity of the method and the accurate measurement of mass variation with temperature. Most of the existing literature studies the determination of vapor pressure, the evaluation of the sublimation enthalpy and the sublimation rate [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A Perkin-Elmer thermogravimetric analyzer was used by Dichi et al to determine the vapor pressure and enthalpy of caffeine sublimation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Karakaya et al used thermogravimetric analysis to determine sublimation enthalpy and vapor pressure within the 570–640 K temperature range of the inorganic compound InCl 3 using CuCl as a reference material [ 8 ]. Thermogravimetric analysis under isothermal conditions was also applied by Shahbazi et al to determine sublimation enthalpy for a series of metal b-diketonate complexes [ 9 ]. Flores et al [ 10 ] demonstrated that the application of thermogravimetric analysis under isothermal conditions is a reliable method for evaluating the enthalpy of sublimation.…”
Section: Introductionmentioning
confidence: 99%
“…In a TG experiment, a sample powder is heated with a fixed heating rate and its weight is constantly measured; from the start of the weight loss in the TG curve, the onset temperature (TG onset ) of precursor vaporization can be seen. [12][13][14] This is a highly valuable information as the TG onset provides us an easily obtained parameter to compare the volatilities of different (organic) precursor compounds and to establish the proper precursor source temperatures (T MLD ) for them to be used in practice in ALD/MLD experiments.…”
Section: Introductionmentioning
confidence: 99%